Incorporating nonlocal parallel thermal transport in 1D ITER SOL modelling. (2nd June 2020) - Wigram, M.R.K.; Ridgers, C.P.; Dudson, B.D.; Brodrick, J.P.; Omotani, J.T.
Abstract: Accurate modelling of the thermal transport in the 'scrape-off-layer' (SOL) is of great importance for assessing the divertor exhaust power handling in future high-power tokamak devices. In conditions of low collisionality and/or steep temperature gradients that will be characteristic of such devices, classical local diffusive transport theory breaks down, and the thermal transport becomes nonlocal, depending on conditions in distant regions of the plasma. An advanced nonlocal thermal transport model is implemented into a 1D SOL code 'SD1D' to create 'SD1D-nonlocal', for the study of nonlocal transport in tokamak SOL plasmas. The code is applied to study typical ITER steady-state conditions, to assess the relevance of nonlocality for ITER operating scenarios. Results suggest that nonlocal effects will be present in the ITER SOL, with strong sensitivity in simulation outputs observed for small changes in upstream density conditions, and drastically different temperature profiles predicted using local/nonlocal transport models in some cases. Global flux limiters are shown to be inadequate to capture the spatially and temporally changing SOL conditions. Introducing impurity seeding, under conditions where detached divertor operation is achieved using the flux-limited Spitzer-Härm models used in standard SOL codes, simulations using the nonlocal thermal transport model under equivalent conditions were found to not reach detachment. An analysis of the connection between SOL collisionality and nonlocality suggests that nonlocal effects will be significant for future devices such as DEMO as well. The results motivate further work using nonlocal transport models to study disruption events and low collisionality regimes for ITER, to further improve accuracy of the nonlocal models employed in comparison to kinetic codes, and to identify more appropriate boundary conditions for a nonlocal SOL model.